2009
DOI: 10.1021/jm900690y
|View full text |Cite
|
Sign up to set email alerts
|

Dopamine D2, D3, and D4 Selective Phenylpiperazines as Molecular Probes To Explore the Origins of Subtype Specific Receptor Binding

Abstract: Assembling phenylpiperazines with 7a-azaindole via different spacer elements, we developed subtype selective dopamine receptor ligands of types 1a,c, 2a, and 3a preferentially interacting with D4, D2, and D3, respectively. To complete this set, the methylthio analogues 2b and 3b exceeding the affinity of 2a and 3a by one order of magnitude and the structural intermediate 1b were synthesized. These chemically similar but biologically divergent target compounds served as molecular probes for radioligand displace… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
139
0

Year Published

2010
2010
2015
2015

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 84 publications
(149 citation statements)
references
References 65 publications
10
139
0
Order By: Relevance
“…The affinities of other compounds remained unchanged or mildly decreased (up to 3.5-fold as for CPD1). These findings are in accordance with those of our previous study (Ehrlich et al, 2009), which demonstrated the D 2L H393…”
Section: Radioligand Displacement Studies To Determine the Influencesupporting
confidence: 94%
See 3 more Smart Citations
“…The affinities of other compounds remained unchanged or mildly decreased (up to 3.5-fold as for CPD1). These findings are in accordance with those of our previous study (Ehrlich et al, 2009), which demonstrated the D 2L H393…”
Section: Radioligand Displacement Studies To Determine the Influencesupporting
confidence: 94%
“…The cDNA of the human dopamine D2 long (D 2L ) receptor was purchased from the Missouri University of Science and Technology cDNA Resource Center (Rolla, MO). The site-directed mutagenesis was performed as described previously (Ehrlich et al, 2009). The D 2L wild-type, D 2L H393 6.55 A, and D 2L H393 6.55 F receptor cDNAs were subcloned into a pcDNA5/FRT vector (Invitrogen) using NheI/XhoI restriction sites.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…We have previously reported that the 3-carbon linked analog of the prototypic D3R selective antagonist, NGB 2904 (N-[4-[4-(2,3-dichlorophenyl)-1-piperazinyl]butyl]-9H-fluorene-2-carboxamide), showed an approximately 100-fold decrease in D3R affinity, but remained D3R selective, as did another 3-carbon linked analog with the 2,3-diCl-substituted 4-phenylpiperazine (Robarge et al, 2001). In contrast, a 2-OCH 3 -substituted 4-phenylpiperazine derivative with a 3-carbon linker has previously been reported to be approximately 14-fold selective for D2R over D3R (Ehrlich et al, 2009). The decrease in D3R affinity in this case was also accompanied by an increase in D2R affinity and could be due to the 2-OCH 3 substitution of the 4-phenylpiperazine bound in the OBS and/or the azaindole as the SP.…”
Section: Discussionmentioning
confidence: 87%